(untitled) (World Bulletin of Social Sciences, 2025)
The Kaltaminor cultural communities occupy a distinctive place in the study of Neolithic societies of Central Asia due to their wide territorial distribution and unique material culture. Since their discovery in the late 1930s, systematic archaeological research has significantly expanded knowledge of their economic basis, settlement patterns, and chronological development. This article analyzes the main stages of the Kaltaminor culture, its local variants, and recent radiocarbon data obtained through international archaeological expeditions. New evidence from the Ayakagytma site suggests that the origins of the Kaltaminor culture should be dated to the mid–7th millennium BCE, earlier than previously assumed. The revised chronology contributes to a deeper understanding of Neolithization processes in western Central Asia.